2008
DOI: 10.1074/jbc.c800140200
|View full text |Cite
|
Sign up to set email alerts
|

Ers1, a Rapidly Diverging Protein Essential for RNA Interference-dependent Heterochromatic Silencing in Schizosaccharomyces pombe

Abstract: Centromeric silencing and heterochromatin formation in Schizosaccharomyces pombe require the RNA interference (RNAi) machinery. Three factors that mediate this mechanism have been identified: 1) the RNA-dependent RNA polymerase complex RdRC, 2) the Argonaute-containing RITS (RNA-induced initiation of transcriptional silencing) complex, and 3) the endoribonuclease Dicer ortholog Dcr1. S. pombe mutants lacking a new factor described here, Ers1, are completely defective in RNAi-dependent silencing of centromeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 13 publications
0
30
0
Order By: Relevance
“…Because no conserved protein motifs were found in Ers1 (26), it was difficult to infer the likely functional involvement of the Ser234 residue. The phenotype of C62 is similar to that of the ers1Δ null mutant; the C62 mutation resulted in derepression of a ura4 + marker gene integrated into the outermost (otr) pericentromeric repeat of chromosome 1 (otr1R::ura4 + ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because no conserved protein motifs were found in Ers1 (26), it was difficult to infer the likely functional involvement of the Ser234 residue. The phenotype of C62 is similar to that of the ers1Δ null mutant; the C62 mutation resulted in derepression of a ura4 + marker gene integrated into the outermost (otr) pericentromeric repeat of chromosome 1 (otr1R::ura4 + ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the mutants, denoted as C62, was found to contain an allele of ers1 (also known as rsh1). Ers1 was previously identified in a candidate KO approach and epistasis mapping as being required for RNAidirected heterochromatic silencing (25,26), but its function in this process was poorly understood.…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that Ers1 is required for silencing at centromeres, but not at the mating type locus and telomeres, consistent with a role in RNAi-dependent heterochromatin formation (9). Ers1 is needed for proper levels of H3K9 methylation as well as the recruitment of the RITS complex to centromeres (9). Deletion of ers1…”
mentioning
confidence: 92%
“…+ also triggers accumulation of noncoding centromeric transcripts and a defect in siRNA production (9). High-throughput analysis demonstrated that ers1 + behaves genetically in a manner similar to silencing factors (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation